(untitled) ("Journal "U". Economy. Management. Finance.", 2022)
Under conditions of instability, inflation has become chronic, which makes it necessary either to develop new tools to combat it, or to find new ways to manage it and benefit from it. In this article we will examine the dual nature of this economic phenomenon through different economic prisms and try to answer the question: inflation is a plus or minus word. This topic is currently very relevant because in 2020 the U.S. has printed a quarter of all existing dollars to the tune of 9 trillion, equivalent to 22% of all U.S. dollars issued since the creation of this nation. This directly affects the world economy, and national markets in particular as the U.S. dollar acts as the world’s reserve currency.